2014
DOI: 10.1097/qai.0000000000000358
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing the PMTCT Implementation Research Agenda in 3 African Countries

Abstract: Countries with high HIV prevalence face the challenge of achieving high coverage of antiretroviral drug regimens interventions including for the prevention of mother-to-child transmission of HIV (PMTCT). In 2011, the World Health Organization and the Department of Foreign Affairs, Trade and Development, Canada, launched a joint implementation research (IR) initiative to increase access to effective PMTCT interventions. Here, we describe the process used for prioritizing PMTCT IR questions in Malawi, Nigeria, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…38–39 The management of a chronic, lifelong, incurable infectious disease in the context of stigma and poverty is challenging for parents and practitioners alike; innovative approaches are needed in the Americas and the Caribbean. 4044 …”
Section: Discussionmentioning
confidence: 99%
“…38–39 The management of a chronic, lifelong, incurable infectious disease in the context of stigma and poverty is challenging for parents and practitioners alike; innovative approaches are needed in the Americas and the Caribbean. 4044 …”
Section: Discussionmentioning
confidence: 99%
“…An exploration of these questions has been identified as a priority in Malawi and elsewhere [6]. In particular, there is an urgent need to understand why a large proportion of women enrolled in the Option B+ programme do not return after the initial visit.…”
Section: Introductionmentioning
confidence: 99%
“…Key challenges for maximizing the effectiveness of HIV/AIDS interventions were reviewed and research questions identified. 5 Following public calls for proposals, 6 IR projects were funded by Global Affairs Canada: all focused on testing approaches for improving rates of retention in care among pregnant women and mothers living with HIV and ensuring their continuation of ART. This reflected the priority given by ministries of health, program implementers, and researchers in each country to the importance of women living with HIV returning to health facilities for routine care, adherence to ART, and improved health outcomes.…”
Section: Introductionmentioning
confidence: 99%